STATE POLICY IN THE FIELD OF SOCIAL AND PEDAGOGICAL SUPPORT OF MATERNITY AND CHILDHOOD IN UKRAINE IN THE FIRST HALF OF THE 20-TH CENTURY - Liudmyla Romanovska (Vasyl Stefanyk Precarpathian National University, 2018)
In the article directions of forming and putting into practice state policy  in the field of social and pedagogical support of maternity and childhood in Ukraine in the first half of the 20-th century are analysed. It is stated that in the first half of the 20-th century in Ukraine state policy was formed on the base of  difficult social and economic situation in Ukraine, that was determined by the consequences of the long First World War, revolution, intervention of the aggressive nearby states and civil wars, that resulted in the severe losses of population,  epidemics, extremely unsatisfactory demographic situation, decline of birth-rate, high level of death rate  especially children`s ones and to disintegration of infrastructure of health protection. Under these circumstances the foundation of the state system of social and pedagogical support of maternity and childhood began its existence in Ukraine: RNK of USR on February, 6, 1919 created Central Board of defence of children, and in June, 14,1919 - Central Board of defence of maternity and childhood was founded as well. These state bodies had to implement  tasks  determining a state course in the field of social and pedagogical support of maternity and childhood: providing  children with good conditions to be born; improvement of children's food; a overcoming high children's death rate; guarantee the children  normal terms of physical, mental and moral development; a fight  against children's neglect, prostitution, criminality, vagrancy;  custody of  problem children; protecting children from violence in families; protection  of maternity and women in the period of pregnancy; raising awareness about  maternity and childhood.The outlined tasks determining a state policy in the field of social and pedagogical support of maternity and childhood were declared in the following legislative resolutions (the decree of RNKof USSR from September, 14,1920 was adopted "On improvement the quality of children's food"; decree of RNKof the USSR"On providing medical establishments, establishments of guard of maternity, schools and child's establishments with food and articles of wide consumption," from February, 8, 1921; declaration of NKO of USSR "On social education" from July, 1, 1920; Decree of RNK of USSR "On children's social inspection" from September, 23,1921; Resolution of SNК of the USSR from May, 31,1935 "On abolishing children's homelessness and neglect"; Resolution of SNК of the USSR from January, 23,1942 "On supervising the children left without parents").The activity of SPONNKO and DSI in the field of social and pedagogical support of maternity and childhood, that aimed at organizing first aid establishments (distribution centers, canteens and homeless shelters ), supporting with individual pedagogical and legal help, creating vacancies of public inspectors of regional, municipal, district levels and others is analysed. Key words: state policy, motherhood, childhood, Ukraine